Il premio Laboratorio Matematico "Riccardo Ricci" 2014-2016 - Barletti, Luigi; Ottaviani, Giorgio (Strumenti per la didattica e la ricerca, 2019)
Si può comprendere la matematica con forbici, colla, spago e mattoncini da costruzione? This volume, which features almost every work from the 2014 and 2016 editions of the Riccardo Ricci Mathematical Laboratory Award, explains how it is possible to understand Mathematics, even using the most advanced technologies such as lasers. The featured works were performed by groups of high school students, under the supervision of the teachers who have personally wrote the drafting. Those are creative and imaginative works, whose reading is recommended to teachers interested in a laboratory approach to Mathematics, as well as to all enthusiasts of the subject. The Award recalls Riccardo Ricci (1953-2013)'s didactic spirit: he was professor of Dynamic Systems at the University of Florence and a point of reference in the city's mathematical community, also thanks to his roles as referent of the Scientific Degree Project and teacher in the courses of teacher training.